2D additive manufacturing via solid state UV cross-linking - Lee, Ivan Kia Wee (Nanyang Technological University, 2024)
This project further investigated UV cross-linking with solid UV cross-linkable resin. A prototype was fabricated for 2D additive manufacturing.